PEMANFAATAN TERAPI SLOW DEEP BREATHING (SDB) TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI : STUDI LITERATUR - Fratama, Ferry Fadli (Jurnal Skala Kesehatan, 2022)
ABSTRACT Background : Hypertension is a condition without symptoms, where abnormally high pressure in the arteries leads to an increased risk of stroke, aneurysm, heart failure, heart attack and kidney damage. Objective: The purpose of this article is to find out the effect of slow deep breathing (SDB) therapy on blood pressure in patients with hypertension. Methods: The method used is to search literature riview done through Google scholar, Science direct and PubMed with article search method using PICOTT. Article searches are limited to full-text articles, national journals and international journals, published in 2018-2022. The search results obtained 207 articles from all databases, 194 Google scholar articles and 13 PubMed articles. Results: The results of this study found 10 articles that fit the criteria of inclusion and exclusion. The results of the literature review show the results of each article that there is an influence of slow deep breathing therapy (SDB) on the blood pressure of patients with hypertension. It is recommended to health workers and families to apply slow deep breathing therapy (SDB) as a complementary therapy to lower the blood pressure of patients with hypertension. Keywords: Slow Deep Breathing Therapy, Blood Pressure, Hypertension